Moderating factors in distant investment of corporate venture capital - Shinhyung Kang; JungTae Hwang (Journal of Open Innovation: Technology, Market, and Complexity, 2019)
The role of venture capital as mediator and gatekeeper is well acknowledged and geographical barriers for open innovation have been questioned, but venture capital firms' distant investments have been investigated only rarely. The strategic benefits accrued from corporate venture capital (CVC) investment depend on the selection of target ventures. Prior research, however, overlooked the incurred information cost for identifying a potential target. Considering that innovative ventures often reside in distant locations, this paper aims to investigate what factors alleviate the information cost for CVCs when identifying target ventures in distant locations. We expect a CVC's target selection in distant locations will be limited to the ventures under a tight appropriability regime, ventures within the same industries as a CVC's business units, and ventures with pre-existing investors that a CVC has prior ties with. The hypotheses are tested with the data on CVC investments in the U.S. between 2006 and 2013. The results empirically support the hypotheses.
Keywords: 650; corporate venture capital; information cost; distant search; partner selection